2021
DOI: 10.1108/jbim-07-2020-0356
|View full text |Cite
|
Sign up to set email alerts
|

How do ESG pillars impact firms’ marketing performance? A configurational analysis in the pharmaceutical sector

Abstract: Purpose This study aims to contribute to international doctrine by testing how environmental social governance (ESG) pillars can affect marketing performance in the pharmaceutical industry. Design/methodology/approach The authors follow a pioneering approach, using a fuzzy-set qualitative comparative analysis and data from the largest European listed companies belonging to the pharmaceutical industry in 2019. Specifically, the authors contribute to international doctrine by testing how ESG pillars can affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 112 publications
(152 reference statements)
0
42
0
1
Order By: Relevance
“…In contrast with this idea, Dalal and Thaker [ 63 ] studied Indian companies included on the NSE 100 ESG Index database for the period of 2015–2017, showing that a good corporate ESG performance improves financial results. Paolone et al [ 64 ] consider market share to be a function of the ESG pillars score, and they use the ESG score as a proxy of the fundamental strategy of corporate sustainability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast with this idea, Dalal and Thaker [ 63 ] studied Indian companies included on the NSE 100 ESG Index database for the period of 2015–2017, showing that a good corporate ESG performance improves financial results. Paolone et al [ 64 ] consider market share to be a function of the ESG pillars score, and they use the ESG score as a proxy of the fundamental strategy of corporate sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…The latter authors concluded that companies with a high level of consumer awareness could increase their value by increasing CSR, if this was accompanied by a good reputation. For Paolone et al [ 64 ], ESG metrics are conducive to a high marketing performance, highlighting the high impact on the governance pillar as an essential determinant for ensuring a higher level of market performance. In parallel, while CSR activities have a negligible or negative impact on company value, the costs sometimes exceed the benefits due to a low advertising intensity [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2004, the World Bank's International Financial Corporation (IFC) laid a cornerstone for the debate with the publication of the report "Who Cares Wins", which provided principles where interpretations of the idea of ESG could stand. Since the release of IFC's report, the construction of the idea of ESG has gained momentumand there is no sign that the movement will cool down (Cappucci, 2018;Clementino & Perkins, 2020;Eccles, Ioannou, & Serafeim, 2014;Paolone, Cucari, Wu, & Tiscini, 2021;Schoenmaker & Schramade, 2019).…”
mentioning
confidence: 99%
“…The results show a positive association between ESG performance and financial performance in particular for studies focused on major companies in developed economies. Paolone et al (2021) have conducted research on the impact of ESG scores on marketing performance for the largest European companies in the pharmaceutical sector using innovative research employing a fuzzy set qualitative comparative analysis. The values of the ESG scores and market share used were those published on Thomson Reuters and Statista.com.…”
Section: Literature Reviewmentioning
confidence: 99%